PREPARING STUDENTS FOR SOCIAL ACTIVITIES BASED ON A DIFFERENTIAL APPROACH - Shodmonova Sevara Muxtor qizi (American Journals, 2024)
This article presents information on preparing students for social pedagogical activities based on a differential approach and highlights the opportunities of differential education.
Keywords: Differential, differential education, differential approach, educational technology, internal differentiation, external differentiation.